2004
DOI: 10.1111/j.1365-2389.2004.00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors relating to soil fertility and species diversity in both semi‐natural and created meadows in the West Midlands of England

Abstract: Metadata onlyThe post-war decline in the area and diversity of neutral meadows in Britain, resulting from agricultural intensification, has prompted schemes to restore and create new habitats. Their success relies on understanding the relations between soil fertility and species diversity. We have investigated these relations, using multivariate analysis, in 28 semi-natural meadows and eight artificially created urban meadows. Mineralizable nitrogen was the most important soil characteristic in the semi-natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…The manure provided nutrients and probably enhanced aeration and microbial activities, which were other causes to increase growth and yield of turmeric. Similar results were obtained in previous studies (Whalen et al, 2000(Whalen et al, , 2003Bhadoria et al, 2003;Hao and Papadopoulos, 2004;McCrea et al, 2004). Darkred soil and gray soil were greatly improved with the application of the manure than red soil (Table 4).…”
Section: Methodssupporting
confidence: 90%
“…The manure provided nutrients and probably enhanced aeration and microbial activities, which were other causes to increase growth and yield of turmeric. Similar results were obtained in previous studies (Whalen et al, 2000(Whalen et al, , 2003Bhadoria et al, 2003;Hao and Papadopoulos, 2004;McCrea et al, 2004). Darkred soil and gray soil were greatly improved with the application of the manure than red soil (Table 4).…”
Section: Methodssupporting
confidence: 90%
“…Gray soil had higher/highest NO 3 -N and NH 4 -N contents, but did not produce a large shoot biomass like dark-red soil, indicating that there was an interaction among the nutrient contents, which infl uenced plant growth. Similarly, other studies (Mazid, 1993;McCrea et al, 2004;Hao and Papadopoulos, 2004) reported that unbalanced nutrient resulted in lower growth and yield of plants. Dark-red soil was comparatively loose (apparent density was the lowest (Table 1)) and it contained optimum moisture, which resulted in greater root and vegetative growth (Table 2).…”
Section: Growth and Yieldmentioning
confidence: 61%
“…Due to the intrinsically low N levels in Patagonian soils (Diehl et al 2003), a small difference in N availability could have a considerable effect on the productivity of the system and consequently on the species richness. It has also been shown that low P availability is a prerequisite for high diversity (Critchley et al 2002;Gilbert et al 2009;Janssens et al 1998;McCrea et al 2004;McCrea et al 2001). An essential difference between the N and P soil cycles is that the available forms of N are easily lost from the system by leaching, fires, and denitrification, while P is bound to the soil.…”
Section: Introductionmentioning
confidence: 99%